Characterization of Continuous-fiber Reinforced Thermoplastics Using Thermoacoustically Excited Ultrasonic Lamb Waves - Webersen, Manuel; Johannesmann, Sarah; Claes, Leander; Henning, Bernd (2016 IEEE IUS~Proceedings)

Vergleich zweier Verfahren der Unsicherheitsabschätzung bei linearisierten inversen Problemen mittels Bayes’scher Inferenz und Pseudoinverse am Beispiel akustischer Transmissionsmessung - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (Sensoren und Messsysteme 2016)

Uncertainty estimation for linearised inverse problems comparing Bayesian inference and a pseudoinverse approach for acoustic transmission measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

GUM-konforme Unsicherheitsabschätzung bei inversen Problemen am Beispiel akustischer Transmissionsmessungen - Feldmann, Nadine; Bause, Fabian; Henning, Bernd

Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, Fabian

Anwendungsm\"oglichkeiten der Schallfeldvisualisierung in der Ultraschallmesstechnik - Olfert, Sergei; Henning, Bernd

5.3.1 - Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, F.; Henning, Bernd

3.2.3 - Direktgravimetrischer Partikelmasse-Sensor zur quasikontinuierlichen Emissionsmessung - Ester, S.; Struschka, M.; Henning, Bernd

An Approach to Non-Destructive Testing of Aged Polymers - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel

Molekularen Schäden auf der Spur - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Kunststoffe)

Detecting Molecular Damage - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Kunststoffe International)

Non-destructive characterization of hygrothermally aged polymers - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel

Ultraschallbasierte Charakterisierung von gealterten Polymeren - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Jahresmagazin Kunststofftechnik 2016)

Zerstörungsfreie Charakterisierung des hydrothermischen Alterungsverhaltens von Polymeren - Webersen, Manuel; Hüttner, Matthias; Bause, Fabian; Moritzer, Elmar; Henning, Bernd
In der zerstörungsfreien Werkstoffprüfung sind bereits zahlreiche Verfahren etabliert, deren Ziel die Detektion makroskopischer Defekt- und Fehlstellen (z.B. Risse, Poren, Fremdeinschlüsse) ist. Insbesondere bei Polymerwerkstoffen muss jedoch auch die Materialalterung auf molekularer Ebene berücksichtigt werden, die sich (zumeist negativ) auf die Materialkenngrößen auswirkt. Gängige Verfahren zur Bestimmung dieser Kenngrößen arbeiten jedoch üblicherweise zerstörend und sind somit beispielsweise für die vorbeugende Instandhaltung oder die Online-Komponentenüberwachung nur eingeschränkt geeignet. In diesem Beitrag wird ein Verfahren zur zerstörungsfreien Charakterisierung des Alterungszustandes von Polymeren vorgestellt. Dazu wird der Zusammenhang zwischen akustisch (zerstörungsfrei, mittels Ultraschall-Transmissionsmessung) bestimmten Kenngrößen und klassisch (zerstörend, z.B. mittels Zugprüfung) bestimmten hydrothermischer Alterung auf das Material Polyamid 6 (PA6) untersucht. Die Ergebnisse Kenngrößen betrachtet. Exemplarisch werden die Auswirkungen zeigen einen engen Zusammenhang zwischen der zerstörend bestimmten Viskositätszahl, die ein Maß für die mittlere Molekülkettenlänge darstellt, und der akustischen Longitudinalwellengeschwindigkeit. Das Molekülkettenabbau (Depolymerisation) bestimmt ist, kann somit auch akustisch und zerstörungsfrei charakterisiert werden. Auf dieser Basis können neuartige, zerstörungsfrei arbeitende Messsysteme entwickelt werden.

Erweiterung des Raman-Nath-Modells zur Analyse von Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (Technisches Messen)

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Analyse integral erfasster rotationssymmetrischer Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Analyse integral erfasster Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (XXIX Messtechnisches Symposium)

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Jurgelucks, Benjamin; Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Model based sensitivity analysis in the determination of viscoelastic material properties using transmission measurements through circular waveguides - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd
Several ultrasonic approaches for material determination are formulated in terms of an (nonlinear) inverse problem, e.g. immersion technique (Castaings et al. (2000)) or plate-waveguide techniques (Marzani et al. (2012)). In this contribution we focus on cylindrical waveguides for ultrasonic material determination and especially on the sensitivity of recorded transmission signals to the material properties. We utilize composite scaled sensitivities to determine the information content that can be achieved by the setup to certain parameters and discuss the limitations of the approach.
Keywords: Sensitivity inverse problem ultrasonic material determination

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)
In this contribution, we present an efficient approach for the transient and time-causal modeling of guided waves in viscoelastic cylindrical waveguides in the context of ultrasonic material characterization. We use the scaled boundary finite element method (SBFEM) for efficient computation of the phase velocity dispersion. Regarding the viscoelastic behavior of the materials under consideration, we propose a decomposition approach that considers the real-valued frequency dependence of the (visco-)elastic moduli and, separately, of their attenuation. The modal expansion approach is utilized to take the transmitting and receiving transducers into account and to propagate the excited waveguide modes through a waveguide of finite length. The effectiveness of the proposed simulation model is shown by comparison with a standard transient FEM simulation as well as simulation results based on the exact solution of the complex-valued viscoelastic guided wave problem. Two material models are discussed, namely the fractional Zener model and the anti-Zener model; we re-interpret the latter in terms of the Rayleigh damping model. Measurements are taken on a polypropylene sample and the proposed transient simulation model is used for inverse material characterization. The extracted material properties may then be used in computer-aided design of ultrasonic systems.
Keywords: viscoelasticity; ultrasonics; guided waves; inverse problem; scaled boundary finite element method

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)

Increasing the sensitivity of electrical impedance to piezoelectric material parameters with non-uniform electrical excitation. - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten (Journal of Sensors and Sensor Systems)

Schallfeldcharakterisierung mittels Schlierentechnik - Olfert, Sergei; Henning, Bernd

Utilizing guided acoustic waves to measure dispersive material properties of polymers - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (AMA~Conferences 2015)
This contribution will give a short introduction to the most important mechanic and acoustic parameters that are necessary to model and simulate frequency dependent sound propagation (dispersion) in isotropic but linear viscoelastic materials. Furthermore, several experimental techniques to measure these parameters will be discussed, like the dynamic-mechanical analysis and transient ultrasonic techniques. Finally it will be shown how to use the determined material parameters for the simulation of transient signals in a highly attenuative acoustic waveguide.

Application of Automatic Differentiation for the inverse parameter identification of complex-valued forward models - Webersen, Manuel; Bause, Fabian; Henning, Bernd

Identification of temperature-dependent model parameters of ultrasonic piezo-composite transducers - Webersen, Manuel; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (AMA Conferences 2015)
When performing measurements, the effects of the measurement system itself on the measured data generally must be eliminated. Consequently, those effects, i.e. the system’s dynamic behavior, need to be known. For the piezo-composite transducers in an ultrasonic transmission line, a model based approach is used to describe their dynamic behavior and take into account its dependence on the environment temperature and the acoustic impedance of the target medium. Temperature-dependent model parameters are presented, which are obtained by performing a multiplepart identification process on the transducer model, based on electrical impedance measurements [1]. The identification process uses an inverse approach for optimizing a subset of the model parameters. Additionally, algorithmic differentiation methods are used to determine accurate derivatives. In a final optimization step, impedance measurements taken at different temperatures are used to determine the temperature dependencies of the model parameters. These can then be used to assess the plausibility of the identification results. Additionally, the parameters can be expressed as polynomials in the temperature to take different operating conditions into account.
Keywords: piezo-composite; transducer; temperature dependency; identification; plausibility

Implementation and uncertainty analysis of a test device for electrical impedance measurements using vector network analyzers - Webersen, Manuel; Karzellek, Michael; Bause, Fabian; Henning, Bernd

Methoden zur Zeit-Frequenz-Analyse bei der Untersuchung dispersionsbehafteter Signale - Bause, Fabian; Rautenberg, Jens; Feldmann, Nadine; Claes, Leander; Henning, Bernd

Rekonstruktion der räumlichen Schallwechseldruckverteilung unter Berücksichtigung der Orthogonalität optischer und akustischer Achsen beim Schlierenverfahren - Olfert, Sergei; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2014)

Time-causal material modeling in the simulation of guided waves in circular viscoelastic waveguides - Bause, Fabian; Schroder, Andreas; Rautenberg, Jens; Henning, Bernd; Gravenkamp, Hauke (2014 IEEE International Ultrasonics Symposium)

Unsicherheitsanalyse eines Vorwärtsmodells zur Simulation transienter Wellenausbreitung im Hohlzylinder - Bause, Fabian; Weber, Daniel; Rautenberg, Jens; Henning, Bernd

Model based sensitivity analysis of Leaky-Lamb wave propagation to the variation of viscous lubricant properties - Bause, Fabian; Brückner, Christoph; Miedl, Jens; Henning, Bernd (Beiträge der 17. ITG/GMA-Fachtagung)

Modellgestützte Analyse des Trocknungsverhaltens von Dispersionslacken aus Daten einer NIR-Multidetektoranordnung - Hoof, Christian; Appelhans, Silke; Henning, Bernd
Zur schnellen und berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung ge-nutzt. In dieser Untersuchung wird das Trocknungsverhalten von Dispersionslack auf einem rauen Substrat mit einer Multidetektoranordnung untersucht. Durch diese Anordnung ist es möglich, gerichtete und diffuse Strahlungsanteile zu detektieren, wodurch zeitvariable Glanzeffekte an der Lackoberfläche miterfasst werden. Mit Hilfe eines Raytracing-Algorithmus wird die Trocknung eines Dispersionslackes simuliert und anhand von Messdaten mit einem FTIR-Spekt-rometer verifiziert.

Sensitivitätssteigerung im Rahmen eines inversen Ansatzes zur Materialparameterbestimmung für Piezokeramiken durch Elektrodenmodifikationen - Unverzagt, Carsten; Henning, Bernd
Simulationen mittels der Finiten Element Methode (FEM) sind heute ein fester Bestandteil im Entwicklungsprozess von Ultraschallsystemen. Durch die simulative Ermittlung der transienten Schwingungsvorgänge können Optimierungen bezüglich gewünschter Zielkriterien vorgenommen werden. Hierdurch lassen sich die aufwendige Prototypenfertigung reduzieren und günstige Entwurfspunkte schneller ermitteln.

On the computation of dispersion curves for axisymmetric elastic waveguides using the Scaled Boundary Finite Element Method - Gravenkamp, Hauke; Bause, Fabian; Chongmin, Song (Computers and Structures)

Modeling and inverse identification of a high bandwidth ultrasonic measurement setup based on piezoelectric 1-3 composites - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Modellbasierte inverse Identifikation von Ultraschall-Transducern anhand der elektrischen Eingangsimpendanz - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Influence of angular radiated ultrasound waves on the Schlieren tomogram - Olfert, Sergei; Claes, Leander; Henning, Bernd (Proceedings of the International Conference on Acoustics)

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Multi Reflection of Lamb Wave Emission in an Acoustic Waveguide Sensor - Schmitt, Martin; Olfert, Sergei; Rautenberg, Jens; Lindner, Gerhard; Henning, Bernd; Reindl, Leonhard (Sensors)

Detection of coatings within liquid-filled tubes and containers by mode conversion of leaky Lamb waves - Schmitt, M.; Schmidt, K.; Olfert, S.; Rautenberg, J.; Lindner, G.; Henning, Bernd; Reindl, L. M. (Journal of Sensors and Sensor Systems)
Abstract. In this paper, a new acoustic sensor principle for coating detection within liquid-filled tubes and containers based on mode conversion of leaky Lamb waves is introduced. Leaky Lamb waves are excited and detected by single-phase transducers, which are attached on the outer side of a tube or container. By transmission time and amplitude measurements, coating formation within the liquid-filled tube and container is detected non-invasively. This new sensor principle is subdivided into the separate considerations of Lamb wave excitation, mode conversion and inverse mode conversion. The Lamb wave excitation by a single-phase transducer is visualized by scanning laser Doppler vibrometer imaging. The mode conversion process of leaky Lamb waves is measured by membrane hydrophone measurements and Schlieren visualization; afterwards, the measured emission angles are compared with the theoretical one. The inverse mode conversion process of pressure waves back to leaky Lamb waves is visualized by Schlieren images. By merging the results of Lamb wave excitation, mode conversion and inverse mode conversion, the new sensor concept is explained. Theoretical considerations and measurement results of adhesive tape coating inside a liquid-filled plastic tube and a liquid-filled stainless steel container verify the new acoustic sensor principle. Finally the measuring sensitivity and the technical realization are discussed.

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd (tm - Technisches Messen)

B5.4 - Signal Processing for Single Transducer Distance Measurement Applications to Reduce the Blind Zone - Schröder, A.; Henning, Bernd

Utilizing ultrasound material parameter determination for the characterization of different stages of ageing in Polyamide 6 - Bause, Fabian; Budde, Christopher; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar
The condensation polymer Polyamide 6 (PA 6) is a thermoplastic resin with high tensile strength and rigidity at comparatively low costs for raw material and processing. This is why PA 6 is a common material for the production of ropes, gears or bearings. Apart from that, a relative new application is the thermoforming of glass fibre laminate sheets with PA 6 as matrix material. The prediction the rest of life period of such high-tech materials is still a research objective. A first step, and also part of this contribution, is the nondestructive investigation of the matrix material. The ageing of PA 6 is mainly affected by thermo- and photo-oxidation as well as post-condensation, which e.g. results in a change of physical properties. For this contribution the acoustical and mechanical material parameters of artificially aged PA 6 have been determined with high frequency ultrasound (1 MHz) and quasi-static experiments. We will give a short description of both experimental setups as well as the ageing procedure. Finally we will discuss the correlation between the experimental results, finding that there is a good correlation between sound velocity and tensile strength.

Ultrasonic Waveguide Signal Decomposition Using the Synchrosqueezed Wavelet Transform for Modal Group Delay Computation - Bause, Fabian; Huang, Boqiang; Kunoth, Angela; Henning, Bernd
Due to the modal behavior of geometrically bounded media, ultrasonic guided waves propagate in waveguides as a combination of multiple dispersive wave packets, which can be simulated as a PDE-problem. Given an excitation in time and space, multiple eigen-modes derived from solving the PDE may propagate each with different dispersion characteristics and weight. Considering a broad-band pulse exciting from one side of a hollow cylindrical waveguide, the received signal at the other side consists of all propagating eigen-modes that can be considered approximately as the narrow band signals. The synchrosqueezed wavelet transform (SWT) is employed to sharpen the time-frequency representation (TFR) of the received waveguide signal. Using a ridge detection algorithm, we successively separate the synchrosqueezed TFR into several narrow band TFRs which can be identified as oscillatory components with time-varying frequency. Then those separated TFRs are reconstructed as narrow band signals using the inverse SWT. Based on an analytical model of the waveguide, we observe that the decomposed signals are similar to those dominant eigen-modes simulated above. Moreover, also the group delay and, therefore, the group velocity of each decomposed signal can be estimated well. This is of high interest when analyzing the characteristic of a given waveguide, such as acoustical property measurements or non-destructive testing.

Utilizing interval-Newton approach for the reliable computation of roots in analytical waveguide modeling - Bause, Fabian; Unverzagt, Carsten; Walther, Andrea; Henning, Bernd